2003
DOI: 10.1093/jnci/djg043
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate End Point for Prostate Cancer-Specific Mortality After Radical Prostatectomy or Radiation Therapy

Abstract: A post-treatment PSA-DT of less than 3 months and the specific value of the post-treatment PSA-DT when it is 3 months or more appear to be surrogate end points for prostate cancer-specific mortality after surgery or radiation therapy. We recommend that consideration be given to initiating androgen suppression therapy at the time of a PSA-defined recurrence when the PSA-DT is less than 3 months to delay the imminent onset of metastatic bone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
257
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(273 citation statements)
references
References 31 publications
14
257
0
2
Order By: Relevance
“…It is strongly associated with prostate cancer-specific and overall survival, 1, 2 and as such is being increasingly used as a prognostic tool by physicians and as an intermediate endpoint in clinical studies. 2,[12][13][14] However, increasingly the dilemma emerges in the setting of rising PSA after radical prostatectomy when physicians and patients do not want to wait a sufficient period of time to calculate PSADT before providing secondary treatment. Indeed, in prior studies, many patients did not have calculable PSADT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is strongly associated with prostate cancer-specific and overall survival, 1, 2 and as such is being increasingly used as a prognostic tool by physicians and as an intermediate endpoint in clinical studies. 2,[12][13][14] However, increasingly the dilemma emerges in the setting of rising PSA after radical prostatectomy when physicians and patients do not want to wait a sufficient period of time to calculate PSADT before providing secondary treatment. Indeed, in prior studies, many patients did not have calculable PSADT.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It has been suggested that PSADT may be a surrogate end-point for prostate cancer death. 2 Consequently, PSADT is increasingly being used as a study end-point and by clinicians caring for recurrent prostate cancer patients. However, to calculate PSADT, patients must be followed long enough to have multiple PSA determinations separated by sufficient time.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of PSA velocity as a surrogate marker being increasingly accepted, such findings may assume greater significance (Carter et al, 2003;D'Amico et al, 2003;Rini et al, 2003). The lower response rate in this study particularly in comparison to newer data from taxanes based studies (Eisenberger et al, 2004;Petrylak et al, 2004) may in part be explained by the fact that the patients in this study were resistant to corticosteroids and oestrogens as well as to androgen deprivation.…”
Section: Discussionmentioning
confidence: 62%
“…10,[13][14][15] Using established PSA-based measures such as bRFS has significantly reduced the maturation time before results from clinical research are considered valid. However, the minimum 24-month follow-up required by the ASTRO consensus criteria 3 is still substantially longer than that might be desired, 16 although brief when compared to the time-frame required to derive mature OS and DSS data.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] While the ASTRO consensus criteria requires a minimum observation period of 2 y, these techniques, which are based on the level of PSA nadir, time to PSA nadir, and absolute PSA thresholds, also require extended follow-up, limiting their clinical utility. 9,10 We have recently demonstrated that time and PSA threshold modeling is effective in prognosticating probability of biochemical recurrence free survival (bRFS) as early as 3 months following curative intent external beam radiation therapy (EBRT). 11 The time and PSA threshold model stratifies patients based upon reaching or failing to reach given PSA thresholds by defined time parameters in follow-up, stratifying the analyzed population by a dichotomous variable at the same relative moment post-therapy.…”
Section: Introductionmentioning
confidence: 99%